Regulation of functions of the brain and body by the principle of predictive coding : implications for impairments of the brain-gut axis - Ohira, Hideki (Array, 2018)
Lisa Feldman-Barrett, who has promoted a psychological constructivism theory of affect, recently proposed the Embodied Predictive Interoception Coding (EPIC) model of affect, based on the perspective of predictive coding. The theoretical framework of predictive coding argues that the brain creates inner models that can provide predictions for perception and motor movement, and that perception and behaviors emerge from Bayesian computations rooted in these predictions. The EPIC model expands this framework to interoception, which is perception of the inner body, and tries to explain the phenomena of affect as integrative experiences based on interoception. This perspective provides important implications for understanding issues of the brain–gut axis and its impairments.